Effect of hot air drying temperature on the quality and antioxidant activity of Boletus edulis Bull.: Fr. Issue 6 (13th April 2021) - Guo, Lei; Lan, Ning; Li, Hua; Xiang, Ping; Kan, Huan
Abstract: In this study, the effects of different hot air drying temperature on the physical properties, chemical components, and bioactive components of dried Boletus edulis were studied. The results showed that higher drying temperature had negative influences on the physical properties and chemical compounds of dried B . edulis, such as dim color, low rehydration ratio, and protein content. There were not significant influences on the content of polysaccharides, polyphenols, and total flavonoids compounds at 50, 60, and 70°C. In addition, the chemical structure of polysaccharide, polyphenol, and total flavonids could be damaged when the drying temperature was over 70°C. At the same time, the antioxidant activities of the three extracts were all decreased. This study indicated that 70°C was the appropriate temperature for hot air drying considering the drying efficiency and quality of B . edulis . Therefore, the results in this paper could provide technical guidance for the practical application of the drying of B . edulis . Practical applications: Hot air drying is the most common processing technology in edible mushrooms industry, and it has the advantages of simple operation and low investment. It has some negative effects on the sensory quality and nutritive value of dried edible mushrooms at high drying temperature. Therefore, the results provided a technical reference for the commercial process of dried Boletus edulis .